2023
DOI: 10.3390/ijms24031931
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of ATP Binding Cassette (ABC) Transporters in Peach (Prunus persica) and Identification of a Gene PpABCC1 Involved in Anthocyanin Accumulation

Abstract: The ATP-binding cassette (ABC) transporter family is a large and diverse protein superfamily that plays various roles in plant growth and development. Although the ABC transporters are known to aid in the transport of a wide range of substrates across biological membranes, their role in anthocyanin transport remains elusive. In this study, we identified a total of 132 putative ABC genes in the peach genome, and they were phylogenetically classified into eight subfamilies. Variations in spatial and temporal gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
3
8
0
Order By: Relevance
“…Similarly, the molecular weight of the CcABC proteins ranged from 6.97 to 345.38. The isoelectric point of the CcABC proteins lies in the range of 4.44 to 10.74 in the same manner as it has been reported in the ABC proteins of plants like Zea mays (Guo et al, 2022), 5.08 to 9.74 strawberry (Shi et al, 2020), 5.4 to 8.96 in cotton (Sun N et al 2021), 4.41 to 10.5 in soyabean (Mishra et al 2019) 5.05 to 10.48 in peach (Sylvia et al 2023)and tomato (Ofori PA et al 2018). In C. cajan, out of 159 CcABC proteins, 105 proteins were basic and 50 were acidic in nature, whereas 2 were neutral proteins.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Similarly, the molecular weight of the CcABC proteins ranged from 6.97 to 345.38. The isoelectric point of the CcABC proteins lies in the range of 4.44 to 10.74 in the same manner as it has been reported in the ABC proteins of plants like Zea mays (Guo et al, 2022), 5.08 to 9.74 strawberry (Shi et al, 2020), 5.4 to 8.96 in cotton (Sun N et al 2021), 4.41 to 10.5 in soyabean (Mishra et al 2019) 5.05 to 10.48 in peach (Sylvia et al 2023)and tomato (Ofori PA et al 2018). In C. cajan, out of 159 CcABC proteins, 105 proteins were basic and 50 were acidic in nature, whereas 2 were neutral proteins.…”
Section: Discussionsupporting
confidence: 75%
“…All the motifs of ABC gene family were highly conserved as reported in peach (Sylvia C et al, 2023), brassica rapa (Yan C et al2017), zea mays (Guo Z et al 2022), soyabean (Huang J et al 2021) and capsicum (Ortiz C et al 2019). It were also mentioned in the pineapple (Chen P et al 2017), hexaploid wheat (Bhati KK et al 2015), barley (Zhang Z et al 2020), strawberry (M. Shi et al, 2020), and flax (Khan et al2020) that all the conserved motifs were identified.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations